2006
DOI: 10.1590/s0102-311x2006001000012
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with cesarean sections in a public hospital in Rio de Janeiro, Brazil

Abstract: Brazil has one of the world's highest cesarean section rates. Contributing factors include the organization of obstetric practice, physicians' attitudes, and women's preferences and decisions. This study aimed to identify factors associated with cesarean sections in a public maternity hospital in Rio de Janeiro. A case-control study was conducted with 231 cesarean sections (cases) and 230 vaginal deliveries (controls). Hierarchical logistic regression analysis was performed, based on a conceptual model. Factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
0
17

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 28 publications
8
24
0
17
Order By: Relevance
“…Other studies have identifi ed them as risk factors, [6][7][8]10 and in the present study this was seen in the public model, except for skin color. As in other child or mother outcomes, 13 better-off women are more likely to have a cesarean section.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Other studies have identifi ed them as risk factors, [6][7][8]10 and in the present study this was seen in the public model, except for skin color. As in other child or mother outcomes, 13 better-off women are more likely to have a cesarean section.…”
Section: Discussionsupporting
confidence: 64%
“…Additional issues associated to cesarean sections are obstetric and newborn factors, which were also identifi ed in other studies 6,10,11,22 as major determinant of cesarean section rate in both groups. However, there were differences according to the category of health service.…”
Section: Discussionmentioning
confidence: 53%
“…Through multivariate logistic regression analyses, the authors found a positive association for cesarean sections in women older than 35 years old (OR = 7.3) and for primiparous women within the multiparous reference category (OR = 6.7). 17 In addition, a sample of 15,336 women in a general hospital (therefore, not a maternity), Padua et al 18 found a significant association for the more advanced age groups, stratified as 20 to 24 years old (OR = 1.26), 25 to 29 (OR = 1.54), 30 to 34 (OR = 1.82), and 35 years and more (OR = 2.05). The same study found a significant association for the married women (OR = 1.25) and for a greater number of prenatal consultations (OR = 1.24).…”
Section: Odds Ratiomentioning
confidence: 99%
“…Igualmente Lopez-Zeno y col. (17) no demuestran algún efecto en la tasa de cesáreas. D'orsi y col. (18) encuentran que la amniotomía, por el contrario, es un factor protector de cesárea, mediante un análisis de regresión.…”
Section: El De Fraser Y Col (2) Es Uno De Los Más Importantes Ensayounclassified